Effect of silver nanoparticles on macrophage cytotoxicity upon exposure to Leishmania tropica in vitro - Al-Saeedi, Rawa F. H.; Saheb, Entsar J. (Iraqi Journal of Science, 2021)
Cutaneous leishmaniasis (CL) is the most form of leishmaniasis disease prevalent in Iraq. CL remains a public health problem in numerous endemic countries because of the absence of safe, effective, and high-cost drugs for treatment. Macrophages are the main inhabitant cell for Leishmania; they phagocyte and allow parasite multiplying. Phagocytosis and anti-leishmanial activity of macrophage are the main factors in the elimination of Leishmania parasites. Phagosome-resident amastigotes also evade innate host defense mechanisms. Silver nanoparticles (Ag NPs) have an important effect in stimulating the production of oxygen species. The objective of this study was to examine macrophages cytotoxicity upon exposure to L. tropica and Ag NPs. Serially diluted concentrations (8, 4, 2, 1, 0.5 and 0.25 μg/ml) of Ag NPs were used following macrophages exposure to L. tropica. MTT assay was used for verification the viability of macrophages and Leishmania (promastigote and amastigote). The viability percentage of macrophages has increased 104.53 ± 4.62% compare with the control group. The results indicated the positive effectiveness of Ag NPs on proliferation of promastigote and amastigotes forms. The IC50 (50% inhibitory concentration) of Ag NPs on promastigotes was calculated 2.988 μg/ ml, and the IC50 of Ag NPs following infection of macrophages in vitro on amastigotes was measured (2.584μg/ml). The current results concluded that )Ag NPs( had an effect on macrophages stimulation to inhibit L. tropica growth in vitro following the infection with parasite.